Debt and cash flow relationship in pecking order theory of corporate financing: dynamic panel evidence - Matemilola, B. T.; Amin Noordin, Bany Ariffin; Md Nassir, Annuar (The Publisher, 2014)
The paper investigates relationship between cash flow and debt. The panel generalized method of moment results reveal that cash flow is negatively related to both long term debt and total debt ratios. Our results support the pecking order theory of corporate financing and imply that there is a need for further development of the capital market to minimize the information asymmetry problem between the firms and the firms’ financiers, to provide firms with easier access to debt and equity financing.